2016
DOI: 10.1111/vde.12343
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intradermal and percutaneous testing to histamine, saline and nine allergens in healthy adult cats

Abstract: Percutaneously (PCT) applied allergens did not cause irritant reactions in healthy cats. PG histamine wheals, although smaller than ID histamine wheals, were easily recognizable and PCT was simple to perform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 10 publications
(26 reference statements)
0
25
0
Order By: Relevance
“…However, a few feline studies have shown that for ≤15 allergens (grass, weed and tree pollens), the concentrations currently used for dogs would be suboptimal, partially explaining the low reactivity in cats. [91][92][93] Likewise, using healthy cats, the optimal concentration of histamine was determined to be 1:50,000 w/v instead of 1:10,000 w/v or 1:100,000 w/v used in dogs. 3,92 Because cats typically demonstrate weak (transient, small) reactions to IDT, the use of intravenously injected dye solutions (Evans blue and fluorescein) has been suggested.…”
Section: Intradermal Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a few feline studies have shown that for ≤15 allergens (grass, weed and tree pollens), the concentrations currently used for dogs would be suboptimal, partially explaining the low reactivity in cats. [91][92][93] Likewise, using healthy cats, the optimal concentration of histamine was determined to be 1:50,000 w/v instead of 1:10,000 w/v or 1:100,000 w/v used in dogs. 3,92 Because cats typically demonstrate weak (transient, small) reactions to IDT, the use of intravenously injected dye solutions (Evans blue and fluorescein) has been suggested.…”
Section: Intradermal Testingmentioning
confidence: 99%
“…undiluted). 93,98 Once the patient is sedated, the lateral thorax is clipped and the sites for the "pricks" are marked. Then, a drop (0.05 mL) of the allergen (or control) is applied and introduced into the skin via the prick device.…”
Section: Intradermal Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study compared irritant reactions of plants, insects, canine dander and moulds using IDT and PT in healthy cats. An irritant reaction to burningbush ( Bassia scoparia) with IDT, but not to any percutaneously tested allergens was reported . A fourth study investigated optimal threshold concentrations of eight allergens including plants, dust mites and storage mites using PT in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite intradermal testing (IDT) being regarded as the gold standard for allergen formulation in ASIT for many years, the serological test was used to reduce interobserver variability inherent in IDT, over the one year study. 28,29 The IgE serological test used contains the alpha chain of the Fc-epsilon receptor (FceR1a) that binds IgE with very high affinity (10 À10 M). Other types of allergen-reactive antibodies, such as IgG, are not able to bind to this receptor.…”
Section: Discussionmentioning
confidence: 99%